SISKEUDES Boosts Accountability and Transparency in Indonesian Village Finances - Ferica Maulidyanto; Sarwendah Biduri (Indonesian Journal of Law and Economics Review, 2024)
This study examines the implementation of the Village Financial System Applications (SISKEUDES) in Sugihwaras, Tenggulunan, and Karang Tanjung to enhance accountability and transparency in village financial reports. Using a qualitative approach with interviews, observations, and documentation, the research found that SISKEUDES significantly improves the efficiency and accuracy of financial reporting compared to manual methods. The application aids budget control and involves the community, fostering greater transparency. The findings highlight SISKEUDES's crucial role in preventing fund misuse and promoting accountable financial management in villages. Highlight: Efficiency: SISKEUDES enhances village financial reporting efficiency and accuracy. Transparency: Community involvement in SISKEUDES promotes transparency. Accountability: SISKEUDES prevents fund misuse, ensuring accountable financial management. Keyword: SISKEUDES, village financial system, accountability, transparency, qualitative research